CHILD CARE AS A DIRECTION OF THEIR SOCIO-CULTURAL MAINTENANCE IN UKRAINE (THE BEGINNING OF THE 20TH CENTURY) - Luparenko, Svitlana (Educological discourse, 2019)
The article is dedicated to the revelation of the purpose and peculiarities of childcare in Ukraine in 1900-1917. Childcare was aimed at ensuring basic protection of children and their care that is necessary for life. It was caused by low level of education and culture of children and their social insecurity. The peculiarities of realization of childcare were the following: taking measures aimed at strengthening children’s health; organization of social work with orphaned children and children deprived of parental care; satisfaction of children’s material needs. Taking measures aimed at strengthening children’s health included provision of hospital care to children, conducting medical examinations of children, examination of children’s institutions, proper arrangement of children’s institutions with educational materials and providing them with rationally constructed furniture, conducting conversations with parents, teachers and children about the necessity of healthy lifestyle, arranging school first aid kits, establishing children’s summer camps, organization of special classes for refugee children during summer holidays. Organization of social work with orphaned children and children deprived of parental care included establishment and maintenance of welfare institutions, identification of the causes of neglecting children and preventing these cases, children’s patronage (children were taken by urban and peasant families that fed and bring them up), support of activity of courts for juvenile offenders (they were in Odesa, Kharkiv and Kyiv). Satisfaction of children’s material needs included creation of free canteens, providing children’s with hot breakfast at educational institutions, rent of apartments for children, providing children with financial aid of different types.